PENGARUH BUDAYA ORAGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN ( Studi Kasus Pada PT. SNS Cabang Madiun) - Budi Santoso; Karuniawati Hasanah (CAPITAL: Jurnal Ekonomi dan Manajemen, 2017)
This study aims to determine the effect of leadership and organizational culture on employee performance at PT. SNS Madiun. The method used in this study using quantitative research methods. And samples used in this study as many as 45 employees. Based on the results of multiple linear regression analysis obtained that the Organizational Culture and Leadership Significant positive influence on employee performance. The better the culture of the organization, then the employee's performance will increase. Leadership positive influence on employee performance means that if the leadership is getting better, then the employee's performance will increase.  Keywords: Organizational Culture, Leadership, Employee Performance